Climate Change and Ocean Acidification: Unraveling the Complex Interactions and Implications for Marine Ecosystems ... : تغير المناخ وتحمض المحيطات: كشف التفاعلات المعقدة والآثار المترتبة على النظم الإيكولوجية البحرية ... - Mohammed Samiullah; Roufa Khanum (OpenAlex, 2024)
Purpose: The study aims to investigate the intricate relationship between ocean acidification and climate change, providing insights into their impacts on marine ecosystems. It seeks to identify sources of greenhouse gases, assess reef vulnerability, and analyze temperature changes' effects on marine biodiversity. Methodology: Quantitative research methods are employed, utilizing data from Bangladesh, the USA, India, and the UK. Dynamic patterns in coral reef health, ocean acidification, greenhouse gas emissions, and marine ecosystem health are assessed between 2019 and 2023. Qualitative analysis supplements the quantitative findings, enhancing understanding of climate change's impacts on marine ecosystems and mitigation strategies. Findings: The study reveals clear patterns in the countries studied, emphasizing the urgency for continuous monitoring and protection of marine ecosystems. It provides insights into how climate change affects marine ecosystems, triggers ocean acidification, and identifies sources ... : الغرض: تهدف الدراسة إلى التحقيق في العلاقة المعقدة بين تحمض المحيطات وتغير المناخ، وتقديم رؤى حول آثارها على النظم الإيكولوجية البحرية. ويسعى إلى تحديد مصادر غازات الدفيئة، وتقييم ضعف الشعاب المرجانية، وتحليل آثار التغيرات في درجات الحرارة على التنوع البيولوجي البحري. المنهجية: يتم استخدام طرق البحث الكمي، باستخدام بيانات من بنغلاديش والولايات المتحدة الأمريكية والهند والمملكة المتحدة. يتم تقييم الأنماط الديناميكية في صحة الشعاب المرجانية وتحمض المحيطات وانبعاثات غازات الدفيئة وصحة النظام البيئي البحري بين عامي 2019 و 2023. ويكمل التحليل النوعي النتائج الكمية، مما يعزز فهم آثار تغير المناخ على النظم الإيكولوجية البحرية واستراتيجيات التخفيف. النتائج: تكشف الدراسة عن أنماط واضحة في البلدان التي تمت دراستها، مع التأكيد على الحاجة الملحة للرصد المستمر وحماية النظم الإيكولوجية البحرية. وهو يوفر رؤى حول كيفية تأثير تغير المناخ على النظم الإيكولوجية البحرية، ويؤدي إلى تحمض المحيطات، ويحدد مصادر انبعاثات غازات الدفيئة. ويؤكد البحث على ضرورة بذل جهود تعاونية لمعالجة آثار تغير المناخ وتعزيز مرونة النظام الإيكولوجي. ...